Understanding the economy-wide efficiency and incidence of major Australian taxes - Liangyue Cao; Amanda Hosking; Michael Kouparitsas; Damian Mullaly; Xavier Rimmer; Qun Shi; Wallace Stark; Sebastian Wende (The Australian Government, The Treasury, 2015)
In recent years, a series of studies have been undertaken in Australia that use static general equilibrium models with a representative household to compare the relative efficiency of different Australian taxes. This paper aims to complement these earlier studies and contribute to a broader discussion about the structure of Australia's tax system by estimating the welfare cost and identifying the economic incidence of marginal changes to the tax system. Our estimates of the additional welfare cost of a marginal tax change (that is, the marginal excess burden) of major Australian taxes largely align with estimates reported in earlier Australian studies. Consistent with earlier studies, stamp duty on conveyances and the company income tax are the least efficient taxes (that is, they have relatively high marginal excess burdens), while the most efficient tax is a hypothetical broad-based land tax. We test the sensitivity of the ranking of the efficiency of major Australian taxes to a range of assumptions about economic agents and the structure of the Australian economy and find that the relative marginal excess burden of major Australian taxes is robust to a wide range of model parameters. Finally, we show that the incidence of major taxes is largely borne by workers through lower real wages caused by lower labour productivity.
Keywords: H21; H22; H30; 330; marginal excess burden; economic incidence; tax revenue